Adaptive changes of swimming crab (Portunus trituberculatus) associated bacteria helping host against dibutyl phthalate toxification. (1st May 2023) - Lin, Weichuan; He, Yimin; Li, Ronghua; Mu, Changkao; Wang, Chunlin; Shi, Ce; Ye, Yangfang
Abstract: The pollution of dibutyl phthalate (DBP) in aquatic environments is becoming an extensive environmental problem and detrimental to aquatic animals. Here, we quantified the response pattern of the bacterial community and metabolites of swimming crab ( Portunus trituberculatus ) juveniles exposed to 0.2, 2, and 10 mg/L DBP using 16 S rRNA gene amplicon sequencing coupled with metabolomic technique. The results showed that DBP changed the bacterial community compositions in a concentration-dependent pattern and decreased the Shannon index at the second developmental stage of the swimming crabs. The Rhodobacteraceae taxa were specifically enriched by crabs when challenged by 2 and 10 mg/L DBP, with an increased in Shannon index and enhanced drift in its assembly. Moreover, DBP changed the metabolic profiling of the swimming crab, highlighted by increased levels of lactate, valine, methionine, lysine, and phenylalanine in the 10 mg/L DBP-exposed crabs. Rhodobacteraceae presented the most considerable contribution to the metabolic potentials in phthalate and benzoate degradation, lactate production, and amino acid biosynthesis. Overall, our results indicated an adaptive change of crab-associated bacteria helped the host resist DBP stress. The findings extend our insights into the relationship between the microbiota and its host metabolism under DBP stress and reveal the potential microbiota modalities for DBP detoxification. Graphical abstract: Image 1 Highlights: Bacterial community changed in a DBP concentration-dependent pattern. DBP increased the Shannon index of Rhodobacteraceae via enhanced drift process. DBP changed the metabolic profiling of the swimming crab. Rhodobacteraceae contributed most to DBP degradation and metabolite biosynthesis.